Underreporting of road traffic accidents: a bibliometric analysis from web of science database - Nor Wazirah Radzman Shah,; Zamira Hasanah Zamzuri, (Penerbit Universiti Kebangsaan Malaysia, 2023)
According to the 2030 Agenda for Sustainable Development Goals (SDGs), the 9th and 11th goals: "Build resilient infrastructure, promote inclusive and sustainable industrialization, and foster innovation," and "Make cities and human settlements inclusive, safe, resilient, and sustainable" are both the vision and mission of the result from this paper are accomplishing for. Although road traffic accidents are a common occurrence in most countries, there is evidence indicating that the number of actual accidents is not properly reported. The proof can be evaluated from a mismatched record between the police and hospital data. This concern has a significant impact on public safety and other components of a country as well. In layman's terms, "underreporting" is the act of reporting fewer numbers than the exact count. In justifying this prevailing research situation, this paper applies the Bibliometric Analysis using the Bibliometrix and Biblioshiny software packages to analyze and visualize the data of a search conducted in the Web of Science Core Collection Database yielded publication results spanning from 1970 to 2023. The results indicate (i) 4,915 papers using the keyword “underreporting”, (ii) 33 papers using the keyword “underreporting of road traffic accidents”, and (iii) 3 papers using the keyword “underreporting of road traffic accidents in Malaysia”. This study is expected to provide an overview of underreporting of road traffic accidents. The impact of underreporting contributes to the setback of incomplete statistical analysis. Although official records are the most useful source of information and exactness, underreporting complements the computation of true results.